Self-Focused Emotions and Ethical Decision-Making: Comparing the Effects of Regulated and Unregulated Guilt, Shame, and Embarrassment. - Higgs, Cory; McIntosh, Tristan; Connelly, Shane; Mumford, Michael (Science & Engineering Ethics, 2020)
Research has examined various cognitive processes underlying ethical decision-making, and has recently begun to focus on the differential effects of specific emotions. The present study examines three self-focused moral emotions and their influence on ethical decision-making: guilt, shame, and embarrassment. Given the potential of these discrete emotions to exert positive or negative effects in decision-making contexts, we also examined their effects on ethical decisions after a cognitive reappraisal emotion regulation intervention. Participants in the study were presented with an ethical scenario and were induced, or not induced, to feel guilt, shame, or embarrassment, and were asked to reappraise, or not reappraise, the situation giving rise to those emotions. Responses to questions about the ethical case were evaluated for the quality of ethical sensemaking, perceptions of moral intensity, and decision ethicality. Findings indicate that guilt, shame, and embarrassment are associated with different sensemaking processes and metacognitive reasoning strategies, and resulted in different perceptions of moral intensity. Additionally, cognitive reappraisal had a negative impact on each of these factors. Implications of these findings for ethical decision-making research are discussed.